Can Wage Subsidies Boost Employment in the Wake of an Economic Crisis? Evidence from Mexico - Bruhn, Miriam (Taylor and Francis, 2020)
This paper measures the employment effect of a program in Mexico that granted firms wage subsidies during the recent economic crisis. I use monthly administrative data at the industry level, along with Euclidean distance matching to construct groups of eligible and ineligible durable goods manufacturing industries that display statistically identical preprogram trends in employment. Difference-in-difference results show a positive but not statistically significant effect of the wage subsidies on employment during the program’s eight-month duration. The size of the effect increases to 18 per cent after the program ended and the results indicate that employment after the program recovered faster in eligible industries than in ineligible industries. Additional analysis suggests that the program did not incentivize firms to retain workers with job-specific skills as originally intended. Instead, the payment of subsidy funds, which only happened towards the end of the program, seems to have provided liquidity for hiring back workers.